Law Enforcement Effectiveness Against Motor Vehicle Theft at Surabaya Metropolitan Police - Ari Setiawan; Noenik Soekorini; Renda Aranggraeni (Penerbit Goodwood, 2026)
Purpose: This study analyzes the effectiveness of law enforcement against motor vehicle theft within the jurisdiction of the Surabaya Metropolitan Police, identifies the factors influencing such effectiveness, and examines efforts to combat the crime.Research Methodology: An empirical legal research method with a sociological juridical approach was employed. Data were collected through document analysis of statutory regulations, official police reports, court decisions, and relevant scientific journals.Results: Law enforcement effectiveness is shaped by five interrelated factors: legal structure, officer capacity, facilities and infrastructure, community participation, and legal culture. Organized fencing networks and increasingly sophisticated offender methods remain the most significant obstacles. Available data indicate an overall crime rate reduction of approximately 4% between 2022 and 2023, with a case clearance rate of 78.9%, though curanmor-specific performance indicators remain largely undisclosed.Conclusions: Improving law enforcement quality, optimizing technology use, and strengthening community participation are essential to reduce motor vehicle theft. Repressive measures under Article 363 of the Criminal Code are the primary legal instrument but require complementary preventive strategies to be fully effective.Limitations: This study is confined to the Surabaya Metropolitan Police jurisdiction and relies primarily on secondary qualitative data, which may restrict the generalizability of findings. Contributions: This study contributes to criminal law scholarship by integrating criminological theory with empirical legal analysis, offering evidence-based insights for crime prevention policy.